Muhammad Bello and the Political System of Leadership in Sokoto Caliphate: A Vital Means for Good Governance in the Contemporary Society - Murtala Hanafi (Bulletin of Islamic Research, 2024)
This study delves into the political system of Muhammad Bello, the visionary second Sultan of the Sokoto Caliphate to uncover valuable lessons for modern governance. Bello's leadership exemplified a unique blend of Islamic principles, intellectual discourse, and strategic expansion. The objectives are to analyze the key features of Bello's political system, examine the impact of his leadership on the Sokoto Caliphate and derive lessons for contemporary society. The paper employed historical research methodology on Bello's reign and critical analysis of primary and secondary sources thereby making a comparative study of Islamic governance models. The study finds that Bello's political system showcased principled leadership guided by Islamic values. Inclusive governance through intellectual discourse, holistic development strategies with strategic expansion and diplomacy. This research contributes to the understanding of Islamic governance, leadership, and development, offering insights for policymakers, scholars, and practitioners seeking to address modern governance challenges.